1994
DOI: 10.1037/0021-843x.103.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of cognitive style among depressed inpatients.

Abstract: An inference from the cognitive theories of depression is that only a subset of depressed individuals should exhibit distinctively negative cognitive styles. Although this inference has been supported by previous research, attempts to characterize these depressives have yielded few identifying variables. This study of psychiatric inpatients and normal control subjects identified several characteristics of depressives with very negative cognitive styles by (a) examining traditional depression subtypes, (b) grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 27 publications
2
66
1
2
Order By: Relevance
“…Childhood maltreatment (i.e., physical, sexual, and emotional abuse) interferes profoundly with normative development and is highly predictive of depression symptoms and disorder in young adulthood (Brown et al 1999;Fergusson et al 1996;Gibb et al 2001;Rose et al 1994;Silverman et al 1996). In a review of several large-scale studies of the impact of childhood maltreatment on later development, Harkness and Lumley (2008) concluded that the presence of childhood maltreatment is associated with a 2-5-fold increase in the risk for later onset of depressive disorder.…”
Section: Childhood Maltreatment Cognitive Organization and Depressionmentioning
confidence: 97%
“…Childhood maltreatment (i.e., physical, sexual, and emotional abuse) interferes profoundly with normative development and is highly predictive of depression symptoms and disorder in young adulthood (Brown et al 1999;Fergusson et al 1996;Gibb et al 2001;Rose et al 1994;Silverman et al 1996). In a review of several large-scale studies of the impact of childhood maltreatment on later development, Harkness and Lumley (2008) concluded that the presence of childhood maltreatment is associated with a 2-5-fold increase in the risk for later onset of depressive disorder.…”
Section: Childhood Maltreatment Cognitive Organization and Depressionmentioning
confidence: 97%
“…En primer lugar, existe una elevada tasa de comorbilidad entre depresi贸n y trastornos de personalidad, oscilando 茅sta entre el 30 y el 70 por ciento (Framer y Nelson-Gray, 1990). En segundo lugar, entre los pacientes depresivos hospitalizados, aqu茅llos con trastornos de personalidad, especialmente el trastorno de personalidad l铆mite, son m谩s propensos a exhibir vulnerabilidad cognitiva que otros pacientes depresivos (Rose, Abramson, Hodulik, Halberstadt y Leff, 1994). Finalmente, es probable que exista un nexo entre vulnerabilidad cognitiva y trastornos de personalidad puesto que muchos diagn贸sticos de trastorno de personalidad son asociados a perfiles cognitivos que representan un riesgo cognitivo para la depresi贸n (e.g., Beck et al, 1990).…”
Section: Vulnerabilidad Cognitiva Y Trastorno De Personalidad Concurrunclassified
“…Bas谩ndose en cuatro argumentos, han sugerido recientemente que la historia de maltrato y desatenci贸n durante el desarrollo evolutivo contribuye a la formaci贸n de riesgo cogn铆tivo hacia la depresi贸n. En primer lugar, Rose et al (1994) hallaron que un subgrupo de pacientes depresivos hospitalizados verbalizaban espont谩neamente cogniciones que suger铆an una elevada vulnerabilidad cognitiva hacia la depresi贸n, tales como "He nacido para ser un miserable" y "Nada ha sido jam谩s bueno para m铆". Una caracter铆stica importante indentificadora de estos individuos era que hab铆an sido sometidos a abuso sexual grave.…”
Section: Maltrato Durante El Desarrollo Y Vulnerabilidad Cognitiva Paunclassified
“…Kuyken & Brewin (1994) reported that, of 35 depressed women who had been abused in childhood, 30 had experienced ' flashbacks ' of the abuse in the previous week. Abuse induces the sorts of cognitive changes that would be expected to mediate the link with adult depression (Rose et al 1994 ;Brewin, 1996). This is an under-researched area as an explanation of sex differences in the experience of depression.…”
Section: Adversity and Vulnerabilitymentioning
confidence: 99%